Evidence for Transmission of Taenia solium Taeniasis/Cysticercosis in a Rural Area of Northern Rwanda - Acosta Soto, Lucrecia; Parker, Lucy Anne; Irisarri-Gutiérrez, María José; Bustos, Javier Arturo; Castillo, Yesenia; Perez, Erika; Muñoz-Antoli, Carla; Esteban, José Guillermo; García, Héctor Hugo; Bornay-Llinares, Fernando Jorge (Frontiers in Veterinary Science, 2021)
Cysticercosis is a parasitic infection caused by the metacestode larval stage (cysticercus) of Taenia solium. In humans, cysticercosis may infect the central nervous system and cause neurocysticercosis, which is responsible for over 50,000 deaths per year worldwide and is the major cause of preventable epilepsy cases, especially in low-income countries. Cysticercosis infection is endemic in many less developed countries where poor hygiene conditions and free-range pig management favour their transmission. A cross-sectional study was conducted in 680 children from a rural primary school in Gakenke district (Northern province of Rwanda). Stool samples were collected from participants and analysed using Kato-Katz method (KK), formol-ether concentration (FEC) and/or copro-antigen enzyme-linked immunosorbent assay (CoAg-ELISA) to detect taeniasis. Blood samples were collected and analysed using enzyme-linked immunoelectrotransfer blot (EITB) and antigen enzyme-linked immunosorbent assay (Ag-ELISA) to detect human cysticercosis. The overall proportion of taeniasis positivity was 0.3% (2/680) and both cases were also confirmed by CoAg-ELISA. A total of 13,3% (76/572) of the children studied were positive to cysticercosis (T. solium-specific serum antibodies detected by EITB), of whom 38.0% (27/71) had viable cysticercus (T. solium antigens by Ag-ELISA). This study provides evidence of the highest cysticercosis prevalence reported in Rwanda in children to date. Systematic investigations into porcine and human cysticercosis as well as health education and hygiene measures for T. solium control are needed in Gakenke district.